EFEKTIVITAS BIRTH PREPAREDNESS AND COMPLICATION READINESS TERHADAP KESIAPAN PERSALINAN PADA IBU HAMIL TRIMESTER III DI PUSKESMAS PASEAN PAMEKASAN - Elga Caesaria Grahardika Andani; Arkha Rosyaria Badrus; Miftahul Khairoh (Jurnal Medicare, 2026)
Background: Birth Preparedness and Complication Readiness (BPCR) is a strategy designed to improve pregnant women’s preparedness for childbirth and potential obstetric complications. Adequate preparation is essential to reduce delays in seeking and receiving appropriate maternal health care. Objective: This study aimed to analyze the effectiveness of BPCR in improving childbirth preparedness among third-trimester pregnant women at Pasean Public Health Center, Pamekasan. Methods: This study used a quasi-experimental design with a one-group pretest-posttest approach. A total of 40 third-trimester pregnant women were selected using total sampling. Childbirth preparedness was measured using a questionnaire before and after the BPCR educational intervention. Data were analyzed using the Wilcoxon signed-rank test. Results: After the intervention, 34 respondents (85.0%) were categorized as prepared for childbirth. The mean preparedness score increased from 61.25 before the intervention to 84.50 after the intervention. The Wilcoxon test showed a statistically significant difference (p<0.001). Conclusion: BPCR was effective in improving childbirth preparedness among third-trimester pregnant women at Pasean Public Health Center, Pamekasan.